A systematic review and meta-analysis of radon risk exposure from drinking water resources in Nigeria - Mohammed, Adamu Usman; Aris, Ahmad Zaharin; Ramli, Mohammad Firuz; Isa, Noorain Mohd; Suleiman Arabi, Abdullahi; Michael Orosun, Muyiwa (Taylor and Francis, 2023)
Elevated radon concentrations in drinking water pose an increased risk of cancer among nonsmokers. A Monte-Carlo Simulation was employed to assess the effective dose and cancer risk associated with radon exposure in humans, utilizing a systematic review and meta-analysis of related studies. These studies were sourced from databases including PubMed, Web of Science, Scopus, Science Direct, and Google Scholar, focusing on drinking water from Nigeria’s six geopolitical zones. The random effects models revealed a 222Rn concentration in drinking water of Nigeria at 25.01, with 95% confidence intervals (CI) of 7.62 and 82.09, indicating significant heterogeneity of (I2 = 100%; p < 0.001). The probabilistic risk of effective dose revealed a best-scenario (P 5%) at Kundiga and Magiro that exceeded the World Health Organization’s (WHO) recommended effective dose limit of 200 µSv/y. Conversely, the worst-case scenario (P 95%) indicated concentrations surpassing the recommended limit at Kundiga, Edbe, Magiro, Ekiti, and Abeokuta. Excess Life Cancer Risk for infants, children, and adults attributed to the ingestion and inhalation of radon from various drinking water sources exceeded the recommended values of 0.2 x 10−3 established by the International Commission on Radiological Protection (ICRP) and the United Nations Scientific Committee on the Effect of Atomic Radiation (UNSCEAR). It underscores the necessity for treating radon-polluted water, employing methos such as aeration and granular activated carbon (GAC) processes.